2020
DOI: 10.1111/ppc.12519
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying among operating room nurses in China: A cross‐sectional survey

Abstract: Purpose: To investigate the prevalence and level of severity of workplace bullying among operating room nurses and to identify the risk factors that contribute to workplace bullying in operating room nurses in China. Design and Methods: This descriptive research was conducted on 411 nurses from six medical centers in Harbin using a structured questionnaire. Findings: The prevalence of workplace bullying was 15.8%. There were significant differences in workplace bullying by sex, hospital level, and marital stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
1
13
2
2
Order By: Relevance
“…Previous research (Ariza-Montes, Arjona-Fuentes, Law, & Han, 2017;Awai, Ganasegeran, & Manaf, 2021;Botha, 2019;Chan et al, 2019;Cunniff & Mostert, 2012;Einarsen & Skogstad, 1996;Giorgi, Ando, Arenas, Shoss, & Leon-Perez, 2013;Hoel & Cooper, 2000;Jones, 2006;Kivimäki, Elovainio, & Vahtera, 2000;Lange, Burr, Conway, & Rose, 2019;Leo, Reid, Geldenhuys, & Gobind, 2014;López-Cabarcos, Vázquez-Rodríguez, & Gieure, 2017;Moreno-Jiménez, Rodríguez-Muñoz, Salin, & Morante, 2008;Namie & Namie, 2018;Niedhammer, David, & Degioanni, 2007;Notelaers, Vermunt, Baillien, Einarsen, & De Witte, 2010;Owoyemi, 2011;Salin, 2018;Salin & Hoel, 2013;Skuzińska, Plopa, & Plopa, 2020;Yadav, Dash, Sinha, & Patky, 2020;Yang & Zhou, 2021) indicated that sociodemographic variables play a role in the experiences of workplace bullying; some of the results are elaborated below.…”
Section: Sociodemographical Variables and Workplace Bullyingmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research (Ariza-Montes, Arjona-Fuentes, Law, & Han, 2017;Awai, Ganasegeran, & Manaf, 2021;Botha, 2019;Chan et al, 2019;Cunniff & Mostert, 2012;Einarsen & Skogstad, 1996;Giorgi, Ando, Arenas, Shoss, & Leon-Perez, 2013;Hoel & Cooper, 2000;Jones, 2006;Kivimäki, Elovainio, & Vahtera, 2000;Lange, Burr, Conway, & Rose, 2019;Leo, Reid, Geldenhuys, & Gobind, 2014;López-Cabarcos, Vázquez-Rodríguez, & Gieure, 2017;Moreno-Jiménez, Rodríguez-Muñoz, Salin, & Morante, 2008;Namie & Namie, 2018;Niedhammer, David, & Degioanni, 2007;Notelaers, Vermunt, Baillien, Einarsen, & De Witte, 2010;Owoyemi, 2011;Salin, 2018;Salin & Hoel, 2013;Skuzińska, Plopa, & Plopa, 2020;Yadav, Dash, Sinha, & Patky, 2020;Yang & Zhou, 2021) indicated that sociodemographic variables play a role in the experiences of workplace bullying; some of the results are elaborated below.…”
Section: Sociodemographical Variables and Workplace Bullyingmentioning
confidence: 98%
“…Previous studies revealed a significant relationship between workplace bullying and marital status. Yang and Zhou (2021), in their study on workplace bullying amongst nurses in China, found that marital status was a determining factor in the bullying process at work; married nurses were more likely to experience workplace bullying. Similarly, in a study by Yadav et al (2020), focusing on the impact of workplace bullying on turnover intention, it was found that amongst Indian school teachers, marital status affects the likelihood of teachers in Indian schools experiencing workplace bullying.…”
Section: Marital Status and Workplace Bullyingmentioning
confidence: 99%
“…Nurses have a very active role in every field of healthcare service present in operating rooms. Nurses are under more pressure and experience more psychological reactions due to the occupational differences in working conditions [31][32][33][34]. Therefore, more satisfied, happier and more productive nurses are important to increase the quality of the service provided.…”
Section: Psychological Risk Factorsmentioning
confidence: 99%
“…In Hong Kong, about 7.7% of clinical nurses reported being bullied by their colleagues in workplaces, including physicians, nurses and other healthcare professionals [ 5 ]. One study in mainland China examined bullying in the Operation Room (OR) and found a prevalence of 15.8%, mainly from patients, patients’ relatives, and physicians [ 6 ]. There is a general lack of research exclusively on LV among nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The study of postmodern feminism has extended gender inequality to the fundamental essence of power inequality, which exists not only among males and females but also among people of the same sex. Much research has focused on workplace bullying of nurses perpetrated by physicians or organizational managers who are predominantly males [ 5 , 6 , 12 ]. Attention should be paid to LV among nurses.…”
Section: Introductionmentioning
confidence: 99%